Assessment of heat tolerance and identification of miRNAs during high-temperature response in grapevine - Zhang, Lipeng; Teng, Yuanxu; Song, Yue; Li, Junpeng; Zhang, Zhen; Xu, Yuanyuan; Fan, Dongying; Wang, Lujia; Ren, Yi; He, Juan; Song, Shiren; Xi, Xiaojun; et al. (Frontiers in Plant Science, 2024)
With global warming, heat stress has been recognized as a significant factor limiting grapevine development and fruit quality. MicroRNAs (miRNAs) are a class of small non-coding RNAs known to play crucial regulatory roles in stress resistance. Hence, there is an immediate requirement to cultivate and identify grapevine varieties that are resistant to heat and explore miRNA-mediated heat-stress defense mechanisms. In this study, we assessed the thermal resistance of 38 grape germplasm resources and identified a series of miRNAs involved in heat stress resistance. The CK (25 ℃) and HS (45 ℃) groups of ‘Shenyue’ cuttings of grapes were used as experimental materials for next-generation sequencing and construct libraries of small RNAs. A total of 177 known and 20 novel miRNAs were detected in libraries. Differential expression analysis identified 65 differentially expressed miRNAs (DEMs) using the DE-Seq procedure. Furthermore, RT-qPCR validation confirmed complementary expression profiles of eight DEMs and their target genes between the HS and CK groups. Heterologous transformation further identified the function of Vvi-miR3633a down-regulated under heat stress in Arabidopsis. In the heterologous expression lines, the survival rate was reduced by high temperature treatment, indicating the ability of Vvi-miR3633a to regulate heat resistance. Assessing the heat resistance of grape species and the expression patterns of miRNA in response to high temperatures may reveal the molecular processes of heat resistance regulation mediated by miRNA in grapes under heat stress.